Quantitative analysis of deformability-based cell separation using deterministic lateral displacement and optical stretching - Holmes, David; Whyte, Graeme; Ekpenyong, Andrew; Guck, Jochen; Duke, Thomas (Proceedings of the 16th International Conference on Miniaturized Systems for Chemistry and Life Sciences, MicroTAS 2012, 2012)
In this work we present data showing deformability-based cell separation in a deterministic lateral displacement (DLD) device. We use cells of defined stiffness (glutaraldehyde cross-linked erythrocytes) to test the performance of the device across a range of cell stiffness and applied shear rates. Optical stretching is used as an independent method of quantifying the stiffness of the cells, thus allowing better understanding of the DLD system for deformability based cell separation. Displacement is shown to correlate with cell stiffness as measured across a range of flow rates. Data showing how the isolation of leukocytes from whole blood varies with shear rate is also presented.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Blood; Cell deformability; Deterministic lateral displacement; Optical stretching; Shear rate